VD_FINDINFO Jug / 2016 / 298 vom 14. März 2016 - VD Tribunal cantonal (2016)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION, VOIES DE FAIT, MENACEDROIT PÉNAL | 123 CP, 126 CP, 180 CP, 219 CP, 42 CP, 43 CP